Association of religiosity on anxiety and depressive symptoms in the Brazilian population: A cross-sectional study - Lucas Lima Galvão; Anne Sulivan Lopes da Silva Reis; Claudio Andre Barbosa de Lira; Marilia Santos Andrade; Katja Weiss; Beat Knechtle; Barbara Juliana Pinheiro Borges; Paulo Gentil; Thomas Rosemann; Rodrigo Luiz Vancini (Acta Psychologica)
Objective: Our aim is to examine the association of religiosity on anxiety and depression symptoms in a convenience sample of female and male Brazilians older than 18 years, and to analyze whether there are sex differences. Methods: Study cross-sectional involved 1017 participants (669 women). Religiosity was assessed using the Duke University Religion Index, evaluating the dimensions of Organizational Religiosity (OR), Non-Organizational Religiosity (NOR), and Intrinsic Religiosity (IR). Anxiety and depression were self-reported on a Likert scale of 1 to 5. Generalized Linear Models with a robust estimator, Poisson distribution, and Prevalence Ratio (PR) estimates with their respective 95 % confidence intervals (CI95%) were used to estimate the PR of depression and anxiety symptoms in the total sample and according to sex. Results: We found that Organizational Religiosity (OR: PR = 1.19; 95 % CI: 1.03–1.39) and Non-Organizational Religiosity (NOR: PR = 1.19; 95 % CI: 1.04–1.36) were associated with depressive symptoms in our sample. However, only Intrinsic Religiosity (IR: PR = 1.60; 95 % CI: 1.30–1.96) was associated with anxiety symptoms. When analyzing differences by sex, we observed that OR (PR = 1.47; 95 % CI: 1.06–2.04) and NOR (PR = 1.48; 95 % CI: 1.13–1.94) were associated with depressive symptoms in male participants. In contrast, for female participants, only IR (PR = 1.03; 95 % CI: 1.01–1.05) was associated with anxiety symptoms. Conclusion: The relationship between religiosity, anxiety, and depression appears to be more influential in shaping the perception of depression among men and the perception of anxiety among women. Therefore, the practice of religiosity should not be discouraged and has the potential to be a complementary therapeutic intervention strategy.